THE ROLE OF SAIDA ZUNNUNOVA IN UZBEK LITERATURE AND HER DESCRIPTION OF WOMEN CHARACTERS - Daminova Kumush Rustam qizi (KONFERENSIYALAR, 2025)
Annotation. Saida Zunnunova is one of the prominent figures of 20th-century Uzbek literature, whose works deeply explore the portrayal of women. As a poet and writer, she vividly captures the inner world of women and the social, spiritual, and psychological struggles they face. Zunnunova does not depict women merely in traditional roles but as strong, independent individuals who possess the ability to define their own destinies and withstand life’s challenges. In her works, women often overcome life’s hardships through their inner strength and perseverance. The poet portrays women through lyrical, realistic, and symbolic means, highlighting their dreams, love, devotion, and personal growth. In Zunnunova’s stories, female characters are shown as active participants in social life, striving for personal transformation and growth. Zunnunova’s literary legacy plays a significant role not only in Uzbek literature but also in the development and enhancement of female representation in literature. She portrays women not just in their traditional family roles but as modern and socially active individuals. Her works emphasize the true role, inner strength, and independence of women, contributing a unique and invaluable perspective to Uzbek literature.